Star excursion balance test scores under different conditions: Effects of arms position and shoe-wear. (April 2022) - Sogut, Bensu; Harput, Gulcan; Tunay, Volga Bayrakci
Abstract: Objectives: The purpose of this study was to investigate the effects of arms position (arms free or hands on the hips) and shoe-wear (with or without athletic shoe) on star excursion balance test (SEBT) scores in healthy physically active individuals. Design: Cross-sectional study. Methods: Fifty-one participants [Age: 22.74 ± 1.93 years; Body Mass Index: 22.52 ± 2.29 kg/m 2 ] were included in the study. The anterior (ANT), posteromedial (PM) and posterolateral (PL) reach directions of the SEBT were performed under four conditions in a randomized order. Within session reliability analysis was performed for each test condition. The composite (COMP) score was calculated as the average of the normalized scores of anterior, posteromedial and posterolateral reach distances. Repeated measures of ANOVA was used for statistical analysis. Results: The ANT and PM reach distances and the composite (COMP) score were found greater with shoes (ANT p = 0.004; PM p < 0.001; COMP p < 0.001). However, the difference in the scores with shoes conditions did not exceed the measurement error. On the other hand, PM and PL reach distances and the COMP score were greater with arms free conditions and the difference in the scores exceeded the measurement error. Conclusions: The results of the study suggest that the differences in the SEBT procedure should be taken into account when comparing the outcomes of different studies. In addition, measurement error values should be considered while interpreting the change in repeated measures of SEBT scores.